Anticariogenic and Antimycobacterial Activities of the Essential Oil of Siparuna guianensis Aublet (Siparunaceae) - de Melo, Daiana Caetano; Miranda, Mayker Lazaro Dantas; Ferreira Júnior, Walnir Gomes; de Andrade, Priscila Mileide; Alcoba, Ana Elisa Teixeira; Silva, Thayná de Souza; Cazal, Cristiane de Melo; Martins, Carlos Henrique Gomes (Orbital: The Electronic Journal of Chemistry, 2017)
Siparuna guianensis is a Brazilian plant with extensive ethnobotanical indication and identified as one of the priority species that should be preserved in the Brazilian Cerrado. This work aimed to investigate the chemical composition and the antibacterial effects of the essential oil from leaves of S. guianensis (SG-EO) grown in southeastern Brazil against a representative panel of oral pathogens and mycobacteria. Anticariogenic and antimycobacterial activities of SG-EO were evaluated in terms of their minimum inhibitory concentrations (MICs). The essential oil from leaves of S. guianensis was analyzed by gas chromatography coupled to mass spectrometry (GC-MS). Forty one compounds were identified, accounting for 92.7 % of the SG-EO composition. E,E-farnesol (18.0 %), β-myrcene (16.0 %), germacrene-D (10.0 %) and siparunone (14.6 %) were the major SG-EO constituents. SG-EO showed the strongest anticariogenic activity against the aerobic bacterium Streptococcus mutans (MIC of 50 µg/mL). SG-EO was also evaluated for its antimycobacterial activity, and showed MIC values of 250 µg/mL against Mycobacterium avium and 500 µg/mL against M. tuberculosis and M. kansasii. These results imply that S. guianensis may be a new alternative source of substances of medicinal interest. This is the first report of anticariogenic and antimycobacterial activities of essential oil of S. guianensis. DOI: http://dx.doi.org/10.17807/orbital.v0i0.930